Quality of Life of Preterm Children: Risk and Protective Factors - Martini, Juliana Aparecida; Padovani, Flávia Helena Pereira; Perosa, Gimol Benzaquen (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, 2016)
Abstract Given the significant increase in survival rates of prematurely born children, this study assessed their quality of life at school age and identified potential risk and protective factors. We included 57 children with premature birth aged 5 to 8 years. Participants completed a cognitive test, and their parents assessed their behavior and quality of life. Most children presented an average or high intellectual level. Despite the mildly compromised quality of life, we observed a high prevalence of behavioral problems in older children. Male participants and behavioral problems were identified as risk factors for lower quality of life; this finding indicates the need to implement systematic monitoring services to facilitate adaptation of premature born children when entering in the school.

Resumen Ante el aumento significativo en las tasas de supervivencia de los recién nacidos prematuros, este estudio tuvo el objetivo de evaluar la calidad de vida de estos niños en edad escolar e identificar posibles factores de riesgo y protección. Cincuenta y siete niños de 5-8 años de edad, nacidos prematuros, contestaron una prueba cognitiva y los padres calificaron su comportamiento y calidad de vida. La mayoría de los niños presentó nivel intelectual promedio o superior. A pesar de pocos daños en la calidad de vida, fue encontrada alta prevalencia de problemas de conducta en los niños mayores. El sexo masculino y problemas conductuales se presentaron como factores de riesgo para la calidad de vida, lo que indica que son necesarios servicios de seguimiento para los niños nascidos prematuros antes que empiecen la escuela, para facilitar su adaptación.

Resumo Considerando-se o aumento significativo nos índices de sobrevida de crianças nascidas prematuras, objetivou-se avaliar sua qualidade de vida em idade escolar e identificar possíveis fatores de risco e proteção. 57 crianças de 5 a 8 anos, nascidas prematuras, responderam a um teste cognitivo e os pais avaliaram seu comportamento e qualidade de vida. A maioria das crianças apresentou nível intelectual médio ou superior. Apesar do leve prejuízo na qualidade de vida, observou-se alta prevalência de problemas de comportamento nas crianças maiores. Identificou-se sexo masculino e problemas comportamentais como fatores de risco para qualidade de vida, sinalizando para a necessidade de serviços de acompanhamento antes do ingresso da criança nascida prematura na escola, visando facilitar sua adaptação.
Calidad de Vida en Niños Prematuros: Factores de Riesgo y Protección
Qualidade de Vida em Crianças Nascidas Prematuras: Fatores de Risco e Proteção
Keywords: quality of life; premature birth; risk factors; childhood development; qualidade de vida; nascimento prematuro; fatores de risco; desenvolvimento infantil